Answer:
![(p+y)(y + z) \\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/bgob9l4r25uojk455gv4qeu78iqrixs5fd.png)
=======================================
Work Shown:
![py + pz + y^2 + yz \\\\(py + pz) + (y^2 + yz) \\\\p(y + z) + (y*y + yz) \\\\p(y + z) + y(y + z) \\\\(p+y)(y + z) \\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/19e6iuv8blbrb1nt4cyw69b7f5kb7z9jz8.png)
I grouped the terms into pairs. Then I factored the GCF from each pair
The GCF of py+pz is p
The GCF of y^2+yz is y
On the last line, I factored out the overall GCF (y+z)
You can use the FOIL rule or the distributive property to expand out (p+y)(y+z) and you should get the original expression back again. This is a way to confirm the correct answer.